Pengaruh ROA, ROE, dan DER Terhadap Pertumbuhan Laba Pada Perusahaan Sektor Industri Tekstil Yang Terdaftar di Bursa Efek Indonesia - Saragi, Nanda Putra (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This study aims to analyze the influence of Return on Assets (ROA), Return on Equity (ROE), and Debt to Equity Ratio (DER) as an independent variable to profit growth as a dependent variable, both partially and simultaneously, in textile industry companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. The research employs multiple linear regression analysis, processed using SPSS version 29. The results indicate that, partially, ROA, DER significantly influence profit growth, inversely proportional to the other 2 variables, the ROE variable has a negative effect on profit growth. Simultaneously, these independent variables contribute substantially to the dependent variable, with a coefficient of determination (R²) value of 99.2%, indicating that almost all variations in profit growth can be explained by ROA, ROE, and DER. The regression model used has passed the classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests, ensuring that the results are reliable, valid, and applicable. This study offers practical implications for company management, particularly in managing assets, equity, and financial structure to optimize profit growth for stakeholders and shareholders. Future researchers are advised to include additional relevant variables, such as liquidity or company size, and to expand the sample size to enhance the generalizability and applicability of the findings.